FACTORS AFFECTING ON BABY'S SUCKING FOR SECRETION OF BREAST MILK AT THE HEALTH CENTER BATUA MAKASSAR - Najmawaty .; Azizah Nurdin (Universitas Islam Negeri Alauddin Makassar, 2014)
This study aims to to obtain a description of the factors that influence the baby's suck-ing of the breast milk in working area of Puskesmas Batua Makassar Health Center.This study is the